2021
DOI: 10.1021/acs.iecr.1c00506
|View full text |Cite
|
Sign up to set email alerts
|

Study on Dispersed-Phase Axial Dispersion in an Agitated–Pulsed Solvent Extraction Column with a Step Tracer Injection Technique

Abstract: In this work, the residence time distribution (RTD) of the dispersed phase (aqueous phase) and continuous phase (organic phase) in an agitated–pulsed extraction column (APC) was measured online with a step tracer injection technique and the axial dispersion was subsequently calculated via RTD analysis. It was found that both the agitation speed and the pulsation intensity had noticeable effects on the axial dispersion of the dispersed phase, which escalates with the increase in the agitation speed and this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The axial dispersion coefficients for both phases were calculated using Tan's method. 15 4 | RESULTS AND DISCUSSION…”
Section: Computational Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The axial dispersion coefficients for both phases were calculated using Tan's method. 15 4 | RESULTS AND DISCUSSION…”
Section: Computational Proceduresmentioning
confidence: 99%
“…ubold0bold-italic−bold1 is set as 0 by assuming that there is no droplet above the dispersed phase inlet. The axial dispersion coefficients for both phases were calculated using Tan's method 15 …”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that all of the drag coefficient models mentioned above were developed for steady motion, which has significant differences from the flow field in industrial equipment. Especially, in extraction columns such as pulsed disks and doughnut columns (PDDCs), , pulsed sieve-plate columns (PSPCs), , Karr reciprocating plate columns, , and agitated-pulsed columns (APCs), , the droplets experience reciprocal acceleration and deceleration due to the input of reciprocating energy. , It has been reported that the unsteady effect accounts for ∼50% of the standard drag coefficient in the range of low Reynolds number …”
Section: Introductionmentioning
confidence: 99%
“…The mass transfer is related to the hydrodynamic characteristics of the pulsed extraction column, such as axial dispersion, [1][2][3][4] holdup, [5][6][7] and slip velocity, 8,9 and the characteristics of mass transfer can affect the extraction behaviors in the column. In liquid-liquid two-phase countercurrent, the main factors affecting and determining the mass transfer process are specific surface area, contact time, and so on.…”
Section: Introductionmentioning
confidence: 99%